What Can We Learn About the Processes of Regulation of Tuberculosis Medicines From the Experiences of Health Policy and System Actors in India, Tanzania, and Zambia? - Kabir Sheikh; Mukund Uplekar (Kerman University of Medical Sciences, 2016)
Background: The unregulated availability and irrational use of tuberculosis (TB) medicines is a major issue of public health concern globally. Governments of many low- and middle-income countries (LMICs) have committed to regulating the quality and availability of TB medicines, but with variable success. Regulation of TB medicines remains an intractable challenge in many settings, but the reasons for this are poorly understood. The objective of this paper is to elaborate processes of regulation of quality and availability of TB medicines in three LMICs - India, Tanzania, and Zambia - and to understand the factors that constrain and enable these processes. Methods: We adopted the action-centred approach of policy implementation analysis that draws on the experiences of relevant policy and health system actors in order to understand regulatory processes. We drew on data from three case studies commissioned by the World Health Organization (WHO), on the regulation of TB medicines in India, Tanzania, and Zambia. Qualitative research methods were used, including in-depth interviews with 89 policy and health system actors and document review. Data were organized thematically into accounts of regulators' authority and capacity; extent of policy implementation; and efficiency, transparency, and accountability. Results: In India, findings included the absence of a comprehensive policy framework for regulation of TB medicines, constraints of authority and capacity of regulators, and poor implementation of prescribing and dispensing norms in the majority private sector. Tanzania had a policy that restricted import, prescribing and dispensing of TB medicines to government operators. Zambia procured and dispensed TB medicines mainly through government services, albeit in the absence of a single policy for restriction of medicines. Three cross-cutting factors emerged as crucially influencing regulatory processes - political and stakeholder support for regulation, technical and human resource capacity of regulatory bodies, and the manner of private actors' influence on regulatory policy and implementation. Conclusion: Strengthening regulation to ensure the quality and availability of TB medicines in LMIC with emerging private markets may necessitate financial and technical inputs to upgrade regulatory bodies, as well as broader political and ethical actions to reorient and transform their current roles.